2018
DOI: 10.1186/s13073-018-0609-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging evidence linking the gut microbiome to neurologic disorders

Abstract: Editorial summaryThe gut microbiome contributes to the development and function of the immune, metabolic, and nervous systems. Furthermore, commensal bacteria modulate symptoms and pathology in mouse models of neuropsychiatric and neurodevelopmental diseases. Uncovering mechanisms that are utilized by the microbiome to mediate gut–brain connections may provide novel opportunities to target therapies to the gut in order to treat neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Recent studies have shown that perturbations in the normal structure of microbiome have a close relationship with human health and disease [ 19 , 31 , 32 ] and there is mounting evidence that alterations of the GI microbiome may influence neurological disorders and autistic behavior [ 48 ]. The shift of microbial communities in the oral cavity in these diseases is being increasingly studied to look at possible early diagnostic markers [ 25 , 35 , 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that perturbations in the normal structure of microbiome have a close relationship with human health and disease [ 19 , 31 , 32 ] and there is mounting evidence that alterations of the GI microbiome may influence neurological disorders and autistic behavior [ 48 ]. The shift of microbial communities in the oral cavity in these diseases is being increasingly studied to look at possible early diagnostic markers [ 25 , 35 , 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent reports further suggest that GI-tract dysbiosis and "leaky gut syndrome" constitute a vastly under-appreciated, under-studied and critical pathophysiological passageway for transport of GI-tract microbiome-derived neurotoxins across GI-tract and blood-brain biological barriers resulting in an age-related progression from systemic inflammation to neurovascular disease to CNS inflammation and degeneration that progressively contribute to critical aspects of neuropathology associated with age-related neurodegenerative disorders. These include neuropathological disorders such as AD, anxiety, autism spectrum disorder (ASD), depression, epilepsy, multiple sclerosis, Parkinson's disease (PD), prion disease, systemic inflammatory response syndrome, and other incapacitating and/or ultimately lethal neurological diseases of the human CNS (Hill et al, 2014a,b;Köhler et al, 2016;Li and Yu, 2017;Varatharaj and Galea, 2017;Zhao et al, 2017aZhao et al, ,b, 2019Griffiths and Mazmanian, 2018;Di Lorenzo et al, 2019;Fox et al, 2019;Patrick et al, 2019;Sarkar and Banerjee, 2019).…”
Section: Gastrointestinal (Gi)-tract and Blood Brain Barrier (Bbb) Dymentioning
confidence: 99%
“…Fourth, in the non-healthy group, we pooled samples from only twelve disease or abnormal bodyweight conditions. Certainly, many more pathological states have been linked to the gut microbiome, including neuro-degenerative and psychiatric disorders [62][63][64] .…”
Section: Discussionmentioning
confidence: 99%